Electroacupuncture Protocol for Sensory and Motor Function Recovery After Orthognathic Surgery: a Randomized Clinical Trial - Itana Lisane Spinato; Taisi da Cunha Antunes; Fabiano Politti; Ruth Ellen Nogueira Izidio; Daniela Aparecida Biasotto-Gonzalez; Delane Viana Gondim (Medical Association of Pharmacopuncture Institute, 2024)
Importance: Orthognathic surgery is utilized to rectify facial deformities, but it can lead to neurosensory alterations. Electroacupuncture has been shown to enhance sensitivity and motor functions in patients post-surgery. However, its application in traumatic facial injuries remains inadequately researched. Objective: To investigate the effects of electroacupuncture on sensitivity and orofacial function in patients undergoing orthognathic surgery.Design, Setting, and Population: A randomized clinical trial involving patients undergoing bimaxillary orthognathic surgery and genioplasty who are randomly allocated to either a physiotherapy (PT) or physiotherapy plus electroacupuncture group (PTEA). Exposures: Participants will be allocated to their respective therapies for a duration of six weeks. The PT group will receive a 50-minute physical therapy session along with 30 minutes of simulated procedure. The PTEA group will receive 50 minutes of physical therapy followed by 30 minutes of electroacupuncture. Main Outcomes and Measures: Before treatment, sensitivity will be assessed using the SMILE Sensitivity Test-BAURU kit, edema will be evaluated using the MD Anderson Cancer Center Head and Neck Lymphedema protocol, range of motion will be measured using a digital caliper, and muscle pain and fatigue will be gauged using numerical scales. The chewing function will be evaluated using the Chewing Quality Assessment Questionnaire. Results: All assessments will be repeated at three and six months following the initiation of treatment. Conclusions and Relevance: This study may provide reliable and high-quality clinical evidence regarding the impact of electroacupuncture on restoring altered sensation and motor function in patients undergoing orthognathic surgery.